Estimates of foil thickness, signal, noise, and nuclear heating of imaging bolometers for ITER. (1st June 2022) - Peterson, B.J.; Nishitani, T.; Reichle, R.; Munechika, K.; O'Mullane, M.G.; Mukai, K.
Abstract: Imaging bolometers have been studied for ITER to serve as a complementary diagnostic to the resistive bolometers for the measurement of radiated power. Two tangentially viewing InfraRed imaging Video Bolometers (IRVB) could be proposed for an ITER equatorial port, one having a view of the entire plasma cross-section (core viewing) and one tilted down 43 degrees from the horizontal to view the divertor (divertor viewing). The IRVBs have 7 cm (horizontal) by 9 cm (vertical) Pt sensor foils, 6 mm × 6 mm apertures, 15 × 20 pixels and focal lengths of 7.8 cm and 21 cm, respectively. Using SANCO and SOLPS models for a 840 m 3 plasma radiating 67.3 MW, synthetic images from the IRVBs are calculated to estimate the maximum signal strengths to be 246 W/m 2 and 62 W/m 2, respectively. We propagate the X-ray energy spectra from the models through the synthetic diagnostics to give the photon energy spectrum for each IRVB pixel, which are used to calculate the fraction of the power absorbed by the foil as a function of foil thickness. Using a criteria of >95% absorbed power fraction, we selected foil thicknesses of 30 μm and 10 μm, respectively. We used these thicknesses and assumed IR systems having 105 fps, 1024×1280 pixels and sensitivities of 15 mK, to calculate the IRVB sensitivities of 3.19 W/m 2 and 1.05 W/m 2, and signal to noise ratios of 77 and 59, respectively. Using the Monte Carlo Nuclear Particle code we calculated for the core viewing IRVB the foil heating by neutrons to be 1.0 W/m 2 and by gammas to be 117 W/m 2 . This indicates that countermeasures may be needed to remove the nuclear heating signal.